On Binary Optimal Control in $H^s(0,T)$, $s < 1/2$ - Manns, Paul; Surowiec, Thomas M. (Comptes Rendus. Mathématique)
The function space $H^s(0,T)$, $s < 1/2$, allows for functions with jump discontinuities and is thus attractive for treating optimal control problems with discrete-valued control functions. We show that while arbitrary chattering controls are impossible, there exist feasible controls in $H^s(0,T)$ that have countably jump discontinuities with jump height one in each of countably many pairwise disjoint intervals. However, under mild assumptions, we show that certain types of jump discontinuities cannot be optimal. The derivation of meaningful optimality conditions via a direct variational argument using simple feasible perturbations remains a major challenge; as illustrated by an example.